Puberty menorrhagia in modern era: analysis in a tertiary care centre - Koranne, Prachi Saurabh; Wahane, Aparna R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Puberty menorrhagia can pose a significant challenge to the gynecologist when associated with serious systemic complications like anaemia and hypoproteinaemia. Early diagnosis and treatment with individualization of each and every case is the keystone in the management of puberty menorrhagia. Exclusion of pregnancy is mandatory in every case, irrespective of the history, reassurance, counseling, regular follow-up along with a balanced nutritional diet and long term iron therapy go a long way in successful management of such cases. Methods: Data was collected from medical case records in each of these cases from indoor case sheets. Results: There were 35 indoor admissions in the gynaecology ward at GMC Akola 2011 to 2013 for critical puberty menorrhagia over a span of two years. The leading cause was anovulatory dysfunctional uterine bleeding. Other systemic associations included hypothyroidism, idiopathic thrombocytopenic purpura, genital tuberculosis, and PCOD. Each case was analyzed for demographic profile, duration of menorrhagia, severity of symptoms, degree of anaemia, final diagnosis, requirement of blood and component therapy and response to conservative management. Conclusions: Most abnormal bleeding in adolescents is caused by immaturity of the hypothalamic - pituitary ovarian axis resulting in anovulation. Approximately 20% of adolescents have an underlying endocrine or haematological disorder requiring targeted diagnostic testing.